EVALUASI KESEHATAN POHON PADA JALUR HIJAU JALAN ARIFIN ACHMAD KOTA PEKANBARU - Loga Mouli Pamula Gumaja; Muhammad Mardhiansyah; Evi Sribudiani (Fakultas Pertanian, Universitas Riau, 2019)
Green line is one way to fulfill the existence of green open space in urban areas, it was covered by various types of plants from land cover crops to trees. The condition of trees in the green lane must be in good condition and healthy so it can comfort the road users. Considering the importance of trees in urban areas, the health of trees must be considered to prevent accidents which caused by trees along the road. The purpose of this research was to evaluate the health of trees on the green lane at Arifin Achmad street, Pekanbaru. This research was conducted by census method and scoring method that consisting of the health and quality of trees along Arifin Achmad street. The quality of trees in the green line at Arifin Achmad in Pekanbaru City were reviewed from stem health (75,59%) it means that the trees on the green lane were healthy. The quality of trees of threats to roads, sidewalks and drainage networks (81,66) classified into light category.